A meta-analysis identifies adolescent idiopathic scoliosis association with LBX1 locus in multiple ethnic groups. Issue 6 (10th April 2014) - Londono, Douglas; Kou, Ikuyo; Johnson, Todd A; Sharma, Swarkar; Ogura, Yoji; Tsunoda, Tatsuhiko; Takahashi, Atsushi; Matsumoto, Morio; Herring, John A; Lam, Tsz-Ping; Wang, Xingyan; Tam, Elisa M S; et al.
Abstract : Background: Adolescent idiopathic scoliosis (AIS) is a common rotational deformity of the spine that presents in children worldwide, yet its etiology is poorly understood. Recent genome-wide association studies (GWAS) have identified a few candidate risk loci. One locus near the chromosome 10q24.31 LBX1 gene (OMIM #604255) was originally identified by a GWAS of Japanese subjects and replicated in additional Asian populations. To extend this result, and to create larger AIS cohorts for the purpose of large-scale meta-analyses in multiple ethnicities, we formed a collaborative group called the International Consortium for Scoliosis Genetics (ICSG). Methods: Here, we report the first ICSG study, a meta-analysis of the LBX1 locus in six Asian and three non-Asian cohorts. Results: We find significant evidence for association of this locus with AIS susceptibility in all nine cohorts. Results for seven cohorts containing both genders yielded P=1.22×10–43 for rs11190870, and P=2.94×10–48 for females in all nine cohorts. Comparing the regional haplotype structures for three populations, we refined the boundaries of association to a ∼25 kb block encompassing the LBX1 gene. The LBX1 protein, a homeobox transcription factor that is orthologous to the Drosophila ladybird late gene, is involved in proper migration of muscle precursor cells, specification of cardiac neural crest cells, and neuronal determination in developing neural tubes. Conclusions: Our results firmly establish the LBX1 region as the first major susceptibility locus for AIS in Asian and non-Hispanic white groups, and provide a platform for larger studies in additional ancestral groups.